An Efficient synthesis of 1-Bromo-1-Cyanocyclopropane. (July 2014) - Xue, Feng; Li, Chang-Gong; Zhu, Yong; Lou, Tian-Jun
An efficient process for the synthesis of 1-bromo-1-cyanocyclopropane has been developed starting from inexpensive γ-butyrolactone via bromination, cyclisation, ammoniation and dehydration reaction. The sequence proceeds in good yield.